2017
DOI: 10.1017/s1431927617005918
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Effectiveness of Atomic Layer Deposited Coatings for the Prevention of Glass Disease

Abstract: Glass disease, the broad term used to describe the process by which historic glass objects degrade, presents a particularly challenging problem for museum curators and conservators. This challenge stems from both an imprecise understanding of how glass disease progresses and a lack of treatment options to slow or stop it. This work is a joint investigation by the University of Maryland, Department of Materials Science and Engineering and the Smithsonian Institution, Museum Conservation Institute that is aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Even under accelerated aging conditions in a laboratory, glass alteration research most often relies on nanoscale analysis or inductively coupled plasma–mass spectrometry techniques to detect and study the progression of glass alteration, as it is seldom advanced enough for the alteration layer to be easily visible using SEM–EDS imaging techniques 28,29 . Museum objects, such as these glass photographic plates, provide a unique opportunity to both visualize, document, and study the development of glass alteration as it has naturally occurred over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even under accelerated aging conditions in a laboratory, glass alteration research most often relies on nanoscale analysis or inductively coupled plasma–mass spectrometry techniques to detect and study the progression of glass alteration, as it is seldom advanced enough for the alteration layer to be easily visible using SEM–EDS imaging techniques 28,29 . Museum objects, such as these glass photographic plates, provide a unique opportunity to both visualize, document, and study the development of glass alteration as it has naturally occurred over time.…”
Section: Resultsmentioning
confidence: 99%
“…Even under accelerated aging conditions in a laboratory, glass alteration research most often relies on nanoscale analysis or inductively coupled plasma-mass spectrometry techniques to detect and study the progression of glass alteration, as it is seldom advanced enough for the alteration layer to be easily visible using SEM-EDS imaging techniques. 28,29 Museum objects, such as these glass photographic plates, provide a unique opportunity to both visualize, document, and study the development of glass alteration as it has naturally occurred over time. Previous work on alteration observed in glass storage vials in biological specimen collections under aqueous conditions at the Smithsonian and a study at the Library of Congress on the early 19th century glass flutes revealed a similar naturally formed depleted alteration layer by SEM.…”
Section: Observable Depletion Region and Its Role In Delaminationmentioning
confidence: 99%
“…Other invasive conservation approaches implying a minimal amount of deposited chemicals have been attempted, with the purpose of stabilizing the hydrated layer with respect to the silicate network hydrolysis (such as in refs. 39,40 ). In this latter approach, the industrial methods consisting of spraying zinc salt solutions on the surface of flat glass 41 have been tested on synthetic unstable glasses subjected to accelerated ageing in climatic chambers.…”
Section: Signs and Issues Of Glass Alteration In Humid Atmospherementioning
confidence: 99%